2000
DOI: 10.1046/j.1365-8711.2000.03687.x
|View full text |Cite
|
Sign up to set email alerts
|

A spectroscopic study of NGC 6251 and its companion galaxies

Abstract: Measurements of the velocities of galaxies thought to be associated with the giant radio galaxy NGC 6251 confirm the presence of a poor cluster with a systemic redshift of z= 0.0244 +/- 0.0004 and a line-of-sight velocity dispersion of sigma_{z}= 283 (+109, -52) km/s. This suggests a cluster atmosphere temperature of T = 0.7 (+0.6, -0.2) keV, which is not enough to confine the radio jet by gas pressure. The core of NGC 6251 shows strong emission lines of [O III] and H alpha + [N II], but there is no evidence f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In addition, there are several candidates outside of our search area. UGC 10604 lies some 52 arcmin southeast of NGC 6251; with z = 0.0252, Werner et al (2000) consider it to be a member of the group. They similarly include UGC 10471a/b (a binary with z = 0.0239 for both members) which is nearly south of the centre.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there are several candidates outside of our search area. UGC 10604 lies some 52 arcmin southeast of NGC 6251; with z = 0.0252, Werner et al (2000) consider it to be a member of the group. They similarly include UGC 10471a/b (a binary with z = 0.0239 for both members) which is nearly south of the centre.…”
Section: Resultsmentioning
confidence: 99%
“…Birkinshaw & Worrall (1993) noted that there were four galaxies lying within of NGC 6251 and it was not associated with a cluster capable of containing an intracluster medium as hot as 5 keV. In a subsequent study, Werner et al (2000) found eight galaxies to be members of the ‘poor group’. In order to search for more candidates and investigate the nature of the objects surrounding NGC 6251, we have obtained spectra of galaxies (brighter than m r ≃ 16) within a 45 arcmin radius using the 2.16‐m optical telescope in Hebei (Xinglong Station of the NAOC).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The linear scale corresponding to 1 milliarcsec (mas) is 0.36 h −1 pc. The line-of-sight velocity dispersion of the sub-cluster is less than 300 km s −1 , implying that it is a poor cluster with an X-ray atmosphere temperature of 0.7 keV (Werner, et al 2000). Combined with plausible densities (consistent with the extended X-ray luminosity measured by Birkinshaw and Worrall (1993)), this gas temperature is far too low to confine any part of the spectacularly linear (e.g., see Figure 1 in Werner, et al (2001)) kpc-scale radio jet.…”
Section: Introductionmentioning
confidence: 99%
“…Spectroscopic observations with HST indicate the presence of a central black hole with a mass of (6 ± 2) × 10 8 M ⊙ (Ferrarese and Ford 1999). Although NGC 6251 is located near the edge of the cluster Zw 1609.0+8212, recent observations by Werner, et al (2000) show that this cluster contains at least three sub-clusters of galaxies that may not be physically related. NGC 6251 is associated with one of these sub-clusters.…”
Section: Introductionmentioning
confidence: 99%